Inteligencia de negocios con Power Bi para toma de decisiones en el área de ventas de Inversiones Díaz E.I.R.L, 2024 - Rojas Lozano, Christian Eduardo (2024)
The research addressed the problem of improving the decision-making process in the sales area of Inversiones Díaz E.I.R.L., due to the inadequate quality of information and long times for preparing and analyzing reports. The objective was to implement a business intelligence solution with Power BI to improve these critical aspects. A mixed approach was used with a pre-experimental design, applying Pre-test and Post-test tests to 23 people involved in decision-making. Three indicators were evaluated: information quality, report preparation time and information analysis time. The results showed significant improvements after the implementation. Information quality increased, with the mean rising from a numerical value of 11.52 in the Pre-test to 23.78 in the Post-test. Report preparation time was reduced from a range of 39-55 minutes to a range of 1-4 minutes, and information analysis time decreased from a range of 15-22 minutes to a range of 5-8 minutes. The t-student test confirmed statistically significant differences in all evaluated indicators. The implementation of Power BI proved to be an effective solution for optimizing decision-making in the sales department, improving information quality and drastically reducing operational times. This study highlights the relevance of business intelligence tools in enhancing decision-making processes, presenting an innovative solution with a positive impact on business efficiency.